Mobile application for Rrefugees - Sanjena Suresh (Nanyang Technological University, 2023)
Refugees are a group of people who are often neglected and forgotten, despite their great numbers across the globe. Like every human being they have needs in life that have to be addressed. Basic necessities are only the bare minimum for one to set up a new life in a foreign land. It is essential for them to integrate into the local community and function as a part of the society there. In order to facilitate that integration, we have to educate them on the language and cultures of the region.